2018
DOI: 10.15226/2372-0948/6/3/00177
|View full text |Cite
|
Sign up to set email alerts
|

The Prevalence of Bovine and Ovine Fasciolosis and the Associated Economic Loss Due to Liver Condemnation in and around Debire Birhan, Ethiopia

Abstract: CA cross-sectional survey was conducted from October 2013 up to March 2014 to assess the prevalence, risk factors and direct economic loss of bovine and ovine fasciolosis in and around Debire Birhan, a town of North shoa Amhara Regional state. In the present study coprology, postmortem examination, questionnaire survey and an abattoir retrospective data were retrieved and analyzed. Seven Kebeles were purposively selected for coprological examination by considering the number of cattle and sheep population of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 0 publications
0
7
0
Order By: Relevance
“…However, mixed infections with both F. hepatica and F. gigant ica are reported where the environment is conducive [13]. Studies have shown that animal fasciolosis occurs in almost all parts of Ethiopia [12][13][14][15][16][17]. Coprological and abattoir surveys conducted in WolaitaSodo town, Ethiopia, for example, indicated that the prevalence of bovine fasciolosis was about 72% [14].…”
Section: Introductionmentioning
confidence: 99%
“…However, mixed infections with both F. hepatica and F. gigant ica are reported where the environment is conducive [13]. Studies have shown that animal fasciolosis occurs in almost all parts of Ethiopia [12][13][14][15][16][17]. Coprological and abattoir surveys conducted in WolaitaSodo town, Ethiopia, for example, indicated that the prevalence of bovine fasciolosis was about 72% [14].…”
Section: Introductionmentioning
confidence: 99%
“…However, our results contradicted with results finding of Karim et al (2015), Isah (2019), andBhutto et al (2012) which shows a higher prevalence of in older than younger cattle. studies show prevalence of 68.08% in old and 55.62% in adult (Ayele et al, 2018). Similarly, Simbwa et al (2014) found 44.8% in adults and 31.8% in sub adults and Japa et al (2020) found more in > 4 years old (17.1%) and low in 2-4 year old (5.6%).…”
Section: Age-wise Prevalencementioning
confidence: 84%
“…The sex wise study shows significantly higher incidence (P<0.05) in male (42.86%) than in female (14.06%) which is supported by Humbal et al (2020), Japa et al (2020) and Isah (2019), whereas contradicted with Ayele et al (2018) and Swarnakar and Sanger (2014) which shows more Fasciola infestation in female and less in male and stated that female animals at different reproductive physiological state such as pregnancy and lactation are immunologically suppressed from increased blood cortisol level which favours the chance of exposure of females to Fasciola infection (Ayele et al, 2018). However, result obtained by Iboyi et al (2017) shows no significant difference between infection of males and females.…”
Section: Sex-wise Prevalencementioning
confidence: 85%
“…The occurrence of Fasciola -infected lymnaeid snails is an indication of fascioliasis transmission sites in the study area. Studies have shown that animal fascioliasis exists in almost all parts of Ethiopia and affect ruminants with a prevalence of 16–60% in coprological samples and 14–91% in abattoir surveys [ 5 , 6 ]. The high prevalence of trematodes infection in the study area could be attributed to the open grazing system.…”
Section: Discussionmentioning
confidence: 99%
“…Studies have shown that animal fascioliasis exists in almost all parts of Ethiopia and affects ruminants, with a prevalence of (16–60%) and (14–91%) in coprological and abattoir surveys, respectively. The higher prevalence was recorded in Bahir Dar using coprological findings (60%) and in Gondar via abattoir surveys (91%) [ 6 , 7 ]. Human fascioliasis is classified as a food-borne trematode infection, commonly acquired by ingesting metacercaria encysted on leaves that are eaten as vegetables.…”
Section: Introductionmentioning
confidence: 99%